Toughness and Maximum Extension of Certain \(t\)-Tough Sets of the Bloom Graph \(B_{m,n}\), \(m\ge 3\), \(n\ge 3\) - Swathi, N. R.; Cynthia, V. Jude Annie (Communications in Mathematics and Applications, 2021)
Data broadcasting is the process of distributing data sets from one or more nodes to other nodes in the network. The fault tolerance of the data broadcasting network plays key importance in its efficient performance. The toughness of graphs is a measure for the fault tolerance of a graph.  In this paper, we investigate the toughness and maximum extension of certain $t$-tough sets of the bloom graph \(B_{m,n}\), \(m\ge 3\), \(n\ge 3\).
Keywords: Toughness; Bloom Graph; Maximum Extension